COMMON FIXED-POINT RESULTS FOR RATIONL TYPE CONTRACTIONS (International Journal of Food and Nutritional Sciences, 2022)
In this study, we demonstrate a few fixed-point results involving contractions of the rational type in thegeneralised 2-Banach space. Our findings broaden standard common fixed-point theorems of contractivetype mappings in the new context.